Improving Security of ID Card and Passport Using Cubic Spline Curve - Abed, Dhiaa Mohammed; Jaber, Abdul Mohsen; Rodhan, Ayad (Iraqi Journal of Science, 2022)
In this paper, the proposes secure system to improving security of ID card and passports is by generating cubic spline co-occurrence code (CCO code) for each ID card. The authentication part, begins passing ID card through the checkpoint then the checkpoint will check the information of card or passport by also extracting features in order to generate the cubic spline co-occurrence code (CCO code), finally comparison is made between extracted CCO code at the checkpoint and CCO code that has been printed on ID card or passport (type of fraud like change personal picture or fraud it’s information). Several tests were conducted to evaluate the performance of the proposed security system. Furthermore, the experiment results reveal that the proposed system can provide high-performance security systems as a result of use. This system can be used in many fields such as security of passport, ID card and certificate. Haralick features (Energy, Entropy, Variance, Contrast, Homogeneity) are very sensitive to any change in the information of ID card or passport, leading to detect any type of forgery.